A radiological study of the sesamoid bones and os meniscus of the cheetah (Acinonyxjubatus) - Kirberger, R. M.; Groenewald, H. B.; Wagner, W. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
A radiological study of the sesamoids was undertaken in differing numbers of joints from 10 cheetahs. Each sesamoid was described and measured. Sesamoids were not found in the elbow and tarsal joints. A sesamoid was found in the abductor digiti 1 longus muscle as well as paired sesamoids were found at the interosseous muscle insertions palmarly of digits #1–5 and plantarly of digits #2–5. There were significant differences between abaxial and axial lengths of some of these sesamoids and the palmar sesamoids were significantly shorter than their plantar counterparts. In the stifle, a patella, a popliteal and two gastrocnemius sesamoids were present. The lateral gastrocnemius sesamoid was significantly longer than the medial one and had a peculiar bilobed appearance. An os meniscus was constantly present in the cranial aspect of the medial meniscus. The shape of the sesamoids and the presence of an os meniscus in the cheetah differed from those seen in the domestic dog and cat and were ascribed to differences in form and function.The radiological appearance of the sesamoids and os meniscus were described in adult cheetahs and compared to the domestic dog and cat. Possible anatomical and physiological factors influencing their appearance are postulated.
Keywords: Sesamoids; os meniscus; cheetah